2015
DOI: 10.1155/2015/124507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Charged Amino Acids on Uncontrolled Seizures

Abstract: Introduction. Epilepsy is one of the most common diseases of the central nervous system. The prevalence of epilepsy throughout the world is 0.5 to 1%, and the same rate is 7.8 per 1000 in Kerman. Almost 20 to 30% of epileptic patients do not respond properly to common medications. The present study investigated patients who did not respond to common and, even in some cases, adjuvant therapies, with two seizures or more per week, regardless of the type of the inflicted epilepsy. Methodology. The participants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…Significant variations were observed in the sum of nitrogen-containing compounds in all four persimmon cultivars. Citrulline was the most abundant amino acid present in high amounts in all samples, ranging between 1777.15 ± 19 μg∙g −1 (PC1) and 2914.29 ± 14.7 μg∙g −1 (PC3), whereas the γ-amino- n -butyric acid compound level was the second highest in all cultivars and it is a vital neurotransmitter, contributing to behavioral functions of the brain [53]. However, β-alanine, ethanol amine, ammonia, and 1-methylhistidine levels were low in all cultivars and collectively constituted 12.1% to 14.9% of all nitrogen-containing compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Significant variations were observed in the sum of nitrogen-containing compounds in all four persimmon cultivars. Citrulline was the most abundant amino acid present in high amounts in all samples, ranging between 1777.15 ± 19 μg∙g −1 (PC1) and 2914.29 ± 14.7 μg∙g −1 (PC3), whereas the γ-amino- n -butyric acid compound level was the second highest in all cultivars and it is a vital neurotransmitter, contributing to behavioral functions of the brain [53]. However, β-alanine, ethanol amine, ammonia, and 1-methylhistidine levels were low in all cultivars and collectively constituted 12.1% to 14.9% of all nitrogen-containing compounds.…”
Section: Resultsmentioning
confidence: 99%
“…However, chronic administration of l -lysine was found to cause tolerance, with maximum protective effects peaking at 10 days of administration and decreasing when treatment time was extended to 20 days [ 146 ]. However, a clinical study by Ebrahimi and Ebrahimi [ 147 ] reported that oral administration of lysine did not reduce seizure frequency in uncontrolled epilepsy patients, suggesting that in addition to bioavailability, the type of seizure is probably relevant.…”
Section: Amino Acidsmentioning
confidence: 99%
“…9 The lamotrigine-pentylenetetrazole kindled mice show resistance toward lamotrigine, phenytoin, and carbamazepine; however, resistance beyond these three drugs is unknown 9 and investigation of its underlying mechanism is recommended by previous studies. 5 To end this, Swiss albino mice were kindled with pentylenetetrazole in the presence of either methylcellulose vehicle or lamotrigine, and the suitability of this model has been evaluated through therapeutic, pharmacokinetic, and neurochemical investigations because reduced bioavailability of antiseizure drugs, 10 impairment in the blood-brain barrier integrity, [11][12][13] and alterations in monoamine and amino acid levels [14][15][16][17] have implicated in drug-resistant epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…To end this, Swiss albino mice were kindled with pentylenetetrazole in the presence of either methylcellulose vehicle or lamotrigine, and the suitability of this model has been evaluated through therapeutic, pharmacokinetic, and neurochemical investigations because reduced bioavailability of antiseizure drugs, 10 impairment in the blood‐brain barrier integrity, 11‐13 and alterations in monoamine and amino acid levels 14‐17 have implicated in drug‐resistant epilepsy.…”
Section: Introductionmentioning
confidence: 99%